Factores organizacionales que influyen al desempeño laboral del personal administrativo en las Instituciones Educativas Públicas en la zona urbana del Distrito de Iquitos 2023 - Vasquez Barboza, Maria Susana (2024)
The purpose of this study was to analyze how organizational factors affect the job performance of administrative workers in public secondary education institutions in the urban area of the district of Iquitos in 2023. This research, of an explanatory type, used a contemporary, multivariate and cross sectional fieldwork design. The study population was composed of 211 administrative workers, of which a sample of 137 was selected by stratified random sampling with proportional affixation. Data were collected through judge-validated surveys and questionnaires and demonstrated acceptable reliability. The results indicated that 51,1% of the administrative staff have deficiencies in managerial leadership, 54% have poor communication, 54,7% experience a poor school climate, and 51,8% show poor work performance in the performance and execution of their main functions. In a multivariate analysis, the binary logistic model revealed that only school climate has a significant influence (p-value < 0,000) on job performance. This suggests that school climate is a determining factor in the work performance of administrative staff in public secondary education institutions in the urban area of the district of Iquitos 2023.